FORMATION OF EFFECTIVE CORPORATE CULTURE AS AN ELEMENT OF PERSONNEL MOTIVATION - Степанова, Е. Р. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The article gives an analysis of the characteristics of corporate culture as an element of motivation. Sequence of actions aimed at the formation of an effective corporate culture has been formed. The effect of nonmaterial motivation, which forms the socio-psychological climate of the team, has been shown.